Fatty acid compositions of the seeds of different Sanguisorba minor genotypes - Kaplan, Mahmut; Tutar, Halit; Kardes, Yusuf Murat; Das, Aydin; Kokten, Kagan (Progress in Nutrition, 2019)
The seed oils of twenty Sanguisorba minor (Leguminosae) genotypes were investigated for their oil contents and fatty acid compositions. The oil contents of the seeds were found to be between 8.85% and 15.66%. The fatty acid compositions of these twenty different genotypes were determined by the GC of the methyl esters of their fatty acids. The oilseeds of Sanguisorba minor genotypes contain palmitic acid as the major component of their fatty acids, among the saturated acids, with small amounts of steraric acid. The major unsaturated fatty acids found in the oilseeds of the genotypes were oleic, linoleic and linolenic acids. In this study, the total saturated fatty acids of Sanguisorba minor genotypes were between 6.40% and 15.84% while the total unsaturated fatty acids were between 84.16% and 93.60%.